Rehabilitation Challenges on Platypnea-Orthodeoxia Syndrome in COVID-19: A Case Report - Rovisco Branquinho, Lurdes; Centro Hospitalar e Universitário de Coimbra (2023)
Platypnea–orthodeoxia syndrome (POS) is characterized by dyspnea and arterial desaturation in the standing or sitting position which is relieved in the supine position. It is a rare post-acute condition in severe coronavirus disease 2019 (COVID-19) survivors, posing additional challenges in the rehabilitation of these patients.A 62-year-old male, recovering from critical COVID-19, presented with worsening dyspnea and positional arterial desaturation while upright on the 36th day of hospital admission, which was significantly impairing early mobilization and functional recovery. Retailored inpatient rehabilitation program included adapted breathing exercises, monitored slowly progressive orthostatism reconditioning, supplemental oxygen therapy and low intensity functional training. After 43 days the patient was discharged, and the rehabilitation program continued without any complication. Dyspnea, strength and functionality scales were used to monitor each phase of the rehabilitation program: Modified Medical Research Council Dyspnea Scale (mMRC) graded 4 in the first assessment, 2 at discharge and 0 after the outpatient intervention, 1 Minute Sit-to-Stand Test scored 25 repetitions in the first outpatient evaluation and 36 at the end of the program and Post-COVID-19 Functional Status Scale graded 4 on the first assessment, 3 at discharge and 1 at the end of the outpatient program.Rehabilitation tailoring is essential and, in patients with severe COVID-19, one of the situations that can interfere with the implementation and progression of the rehabilitation program is POS, which must be considered whenever there is positional dyspnea or arterial desaturation after an initial period of clinical improvement.